Chile : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Politics: President Bachelet won the Presidential election on a platform to foster inclusive growth and reduce inequality. Her government took office in March 2014 and is launching an ambitious policy agenda that includes important reforms in several areas, including taxation, education, productivity, and energy. Outlook and risks: Chile's global environment is shifting, with a dimmer outlook for its main export, copper, and normalization of global monetary conditions. Growth has slowed markedly, resulting in a modest output gap. The peso has depreciated, feeding into inflation. Staff projects growth to bottom out in 2014 and then gradually recover. Key risks relate to a large and lasting drop in copper prices and global financial volatility. Policy mix: The freely floating peso is working as a shock absorber and will support the economic recovery. The policy mix with broadly neutral fiscal and accommodative monetary policy is appropriate. Room for further monetary easing has narrowed but space remains if domestic demand flounders, so long as inflation expectations remain well anchored. On fiscal, given the strong public finances, automatic stabilizers should be allowed to operate unimpeded and there is space for stimuli in the event of a major downturn. The commitment to close the structural fiscal deficit by 2018 is appropriate and should be phased in a way that avoids undue drag on the recovery. Should risks materialize, the freely floating currency is the first line of defense. Growth and equity reforms: Achieving strong growth while reducing inequality will require structural reforms. The authorities' agenda focuses on the right areas but many details remain work in progress. Clarity on the details, timetables, and prioritization will reduce uncertainty and the risk of delays. Financial stability: Risks to financial stability appear contained, but it will be important to push through with regulatory reforms underway, including initiatives currently in Congress. Further effort will be needed to close regulatory gaps, in particular bank capital requirements, relative to international benchmarks.